MOTIVASI PETUGAS KESEHATAN, PRILAKU IBU HAMIL DAN PERAN KELUARGA TERHADAP KEPATUHAN KONSUMSI TABLET BESI DI KOTA KEDIRI - Erma Retnaningtyas (STRADA : Jurnal Ilmiah Kesehatan, 2016)
Anemia iron defficiency Iron Deficiency Anemia is one of the main nutritional problem in Indonesia, which accounts for mortality in pregnant women. To overcome these problems the government has been implementing a program providing iron tablets to pregnant women. Uncompliance consume iron tablet is a phenomenon which causes the high cases of pregnancy induced anemia. This research was conducted in 9 Puskesmas in Kediri city to determine the relationship of health provider motivation and behavior of pregnant women and the role of families with amount consumptions iron tablet. Type of research is descriptive analytic survey using cross section with a sample of 59 pregnant women Trimester I have get iron tablets and average visits of pregnant women for 1 month. Data collected with interviews using questionnaires and compliance observation sheet. Hypotheses using Chi Square test and Multiple Linear Regression. The results showed 54.2% of pregnant women are not subservient to consume the amount of iron tablets. Chi - square analysis of the data obtained (p = 0.000 <0.05) No relationship between motivation of health provider, (p = 0.332> 0.05) there is no relationship and behavior of pregnant women (p = 0.264> 0.05) there is no relationship role families with compliance consumption of iron tablets. Results Multiple Linear Regression obtained (p <0.05) together there is a significant relationship between health worker motivation and behavior of pregnant women with anemia of pregnancy. Health provider must give health education abaut the benefits and how to consumption iron tablets. Motivating pregnant women to increase compliance to consume iron tablets to involve the family so as to reduce the incidence of anemia in pregnancy